Evaluasi Pelayanan Akademik pada Perguruan Tinggi Swasta Prodi Teknik Industri Menggunakan Metode IPA dan SERVQUAL - Fithriya Nur Hana; Ferida Yuamita (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study provides insights for improving academic service quality and enhancing student satisfaction. The Industrial Engineering Program aims to enhance academic service quality to support students’ success. Recent survey data indicate a decline in satisfaction, with a 9.11% drop from 2021/2022 to 2022/2023 (from an average score of 4.39 to 3.99) and a further 20.80% decline from 2022/2023 to 2023/2024 (down to 3.16). This study analyzes service quality using SERVQUAL and IPA methods across 22 service attributes to identify areas needing improvement. Results show all attributes with a negative gap, with the smallest gap in academic advising (P10) at -0.76, indicating it is closest to meeting student expectations. The IPA framework categorizes improvements into four quadrants, prioritizing restroom cleanliness, laboratory facilities, and classroom comfort (Quadrant 1). Suggestions include aligning service attributes more closely with student needs and exploring how service quality impacts academic performance and well-being. This research provides key insights to enhance service quality and student satisfaction in the future.